Redesain ekologis Kawasan Wisata Danau Sanggu Kabupaten Barito Selatan berbasis konsep waterfront - Agustina, Gloria; Gunawan, Andi; Hadi, Akhmad Arifin (Jurnal Arsitektur Lansekap; Vol. 10, No. 1 April 2024, 2024)
Sanggu Lake Tourism Area, located in South Barito Regency, Central Kalimantan, plays an important role in providing green open space for recreational and relaxation activities. The lack of management and changes in building orientation reduce the quality of the site and pose threats to environmental damage. Therefore it is necessary to redesign the waterfront area with an ecological approach to reduce environmental impact. The purpose of this research is to identify site character, analyze the potential and constraints on the site, to develop an ecological design concept, and to ecologically design the Sanggu Lake Tourism Area based on the waterfront concept. The stages of the research include the process of preparation, inventory, analysis and synthesis, and design. Collecting data through surveys, literature studies, interviews, and questionnaires. The basic concept of the research is "Ranu Welum" or Water of Life which is revealed to be 3 basic values, namely socio-cultural center, ecological park, and recreational waterfront. The design concept is taken from the typical Dayak motif, namely "Batang Garing" or the Tree of Life and implemented in spatial patterns, circulation, and vegetation. Ecological design is applied by implementing ecological principles based on community preferences. The results of the study are area redesign consisting of reception zones, tourist zones I, tourist zones II, relaxation zones, play zones, exercise zones, and service zones.